2021
DOI: 10.1021/acs.macromol.0c02370
|View full text |Cite
|
Sign up to set email alerts
|

Localized and Collective Dynamics in Liquid-like Polyethylenimine-Based Nanoparticle Organic Hybrid Materials

Abstract: Broadband dielectric spectroscopy, rheology, and nuclear magnetic resonance spectroscopy are employed to study molecular dynamics in a nanoparticle organic hybrid material (NOHMs) system comprising 20 wt % silica nanoparticles ionically bonded to a polyethylenimine canopy. By comparing the neat polymer (used as a canopy) to the derivative NOHMs, we find that timescales characterizing segmental dynamics in the NOHM are identical to those for the neat polymer. Detailed analysis of the carbon-spin lattice relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 66 publications
2
35
0
Order By: Relevance
“…NOHMs boast a high degree of chemical and physical tunability, with a wide range of nanocore–canopy combinations possible for a variety of functionalities. They exhibit negligible vapor pressure and a higher thermal and oxidative stability compared to those of their constituent polymers. NOHMs were initially developed by Archer et al as electrolyte additives to suppress dendritic growth in battery applications and were explored by Park et al as anhydrous CO 2 capture solvents. , The synthesis, dynamics, and CO 2 capture mechanisms of various classes of NOHMs have been extensively investigated. , NOHMs interact with other chemical species based both on enthalpic and entropic contributions, which are influenced by the functional groups along the polymer chains and the structural configurations of the NOHMs’ polymeric canopy, respectively . Recently, NOHM-based fluids have been explored as potential novel electrolytes in electrochemical applications and for combined CO 2 capture and conversion , based on their ability to complex redox-active species and selectively capture CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…NOHMs boast a high degree of chemical and physical tunability, with a wide range of nanocore–canopy combinations possible for a variety of functionalities. They exhibit negligible vapor pressure and a higher thermal and oxidative stability compared to those of their constituent polymers. NOHMs were initially developed by Archer et al as electrolyte additives to suppress dendritic growth in battery applications and were explored by Park et al as anhydrous CO 2 capture solvents. , The synthesis, dynamics, and CO 2 capture mechanisms of various classes of NOHMs have been extensively investigated. , NOHMs interact with other chemical species based both on enthalpic and entropic contributions, which are influenced by the functional groups along the polymer chains and the structural configurations of the NOHMs’ polymeric canopy, respectively . Recently, NOHM-based fluids have been explored as potential novel electrolytes in electrochemical applications and for combined CO 2 capture and conversion , based on their ability to complex redox-active species and selectively capture CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Several specialized techniques have been developed to study the mechanical properties of ultrathin films, including so-called bubble inflation and buckling measurements, which have been used to characterize unique behavior induced by substrate interactions, including glassy softening 25,26 and rubbery stiffening. 27,28 Broadband dielectric spectroscopy was recently used in conjunction with NMR 29 to infer information about the mobility of specific regions of PEI under different conditions, i.e., backbone, side chain, and chain end mobility in the bulk vs in confined composites. Neutron scattering has also been employed to provide particularly rich information about the nature of PEI mobility within different mesoporous composites as a function of polymer loading and pore functionality.…”
Section: Introductionmentioning
confidence: 99%
“…However, these techniques are often either not sensitive enough to determine transitions in thin films or at low polymer loadings in composites or they are of limited application for probing polymer properties within nanoconfined pores. Several specialized techniques have been developed to study the mechanical properties of ultrathin films, including so-called bubble inflation and buckling measurements, which have been used to characterize unique behavior induced by substrate interactions, including glassy softening , and rubbery stiffening. , Broadband dielectric spectroscopy was recently used in conjunction with NMR to infer information about the mobility of specific regions of PEI under different conditions, i.e ., backbone, side chain, and chain end mobility in the bulk vs in confined composites. Neutron scattering has also been employed to provide particularly rich information about the nature of PEI mobility within different mesoporous composites as a function of polymer loading and pore functionality. However, given the vast number of parameters that can influence aminopolymer mobility in DAC systems, the development of sensitive benchtop techniques that can provide additional or complementary information to the aforementioned methods concerning mobility in nanoconfinement would be of significant value for advancing the field.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids, [ 4,6,16,17 ] deep eutectic solvents, [ 3,6,18–21 ] microemulsions, [ 22–26 ] , and nanoparticle organic hybrid materials (NOHMs) [ 9,10,27–30 ] are currently being developed as novel electrolyte materials to improve the performance of various electrochemical systems. In particular, NOHMs consist of a polymer that is either ionically [ 31–38 ] or covalently tethered [ 31–33 ] to a nanoparticle core and possess a number of favorable properties including negligible vapor pressure, [ 31 ] oxidative thermal stability, [ 31,39–41 ] chemical tunability [ 9,42 ] and high ionic conductivity. [ 27,43 ] As a result, NOHMs have been extensively studied as water‐lean CO 2 capture solvents and it has been shown that the organized structure of the polymer canopy in NOHMs leads to significantly less swelling compared to the untethered polymer, upon exposure to CO 2 .…”
Section: Introductionmentioning
confidence: 99%